Fiber optic sensing for offshore engineering applications - Sjamsudin, Wendy Wijaya (2018)
A floating production storage and offloading (FPSO) unit is a floating ship used by the offshore oil and gas industries for the production and processing of hydrocarbons as well as for storing oil. It is compulsory to monitor the degradation of structural health of FPSO caused by waves and still water and by the harsh environment in which the FPSO is operational.